The Moderation Effect of Processing Efficiency on the Relationship Between Visual Working Memory and Chinese Character Recognition - Xu, Zhengye; Wang, Li-Chih; Liu, Duo; Chen, Yimei; Tao, Li (Frontiers in Psychology, 2020)
To investigate the underlying mechanism of the relationship between visual working memory (VWM) and Chinese character recognition, and the moderation effect of processing efficiency on this relationship, 154 first-grade students were administered a battery of tasks for VWM, rapid temporal processing, and Chinese character reading. In the VWM task, the children were asked to remember the jumping routes of a frog and report these routes in reverse sequence. The longest span for which each participant could respond correctly at least four times out of six was the VWM index. In the task of temporal order judgement, the participants were asked to select which of two balls was presented first, with stimulus onset asynchronies varying from 8 to 492 ms according to an adaptive psychophysical procedure. Visual temporal order threshold (VTOT) was utilized as an indicator of processing efficiency. The participants were asked to read 100 characters aloud to measure their word-level reading abilities in Chinese character recognition. After controlling age, non-verbal intelligence, visual short-term memory, morphological awareness, and orthographic awareness, the results of a moderation effect analysis showed that 1) both VWM and visual VTOT predicted Chinese character reading, and 2) the moderation effect of VTOT on the VWM-reading link was significant (p = .001). The correlation between VWM and Chinese character reading was positive and significant when VTOTs were above average (i.e., smaller than 87.14 ms); however, the correlation was negative at relatively poor levels of VTOTs (i.e., larger than 231.44 ms).